Solving the climate crisis through social change public investment in social prosperity to cool a fevered planet - Lipow, Gar W. (Santa Barbara, Calif. Praeger, 2012)
"This book presents an accessible and easy-to-follow argument that the climate crisis is a side effect of inequality and injustice, and demonstrates how strategies such as large-scale social investment will prove far more effective in reducing greenhouse gas pollution than cap-and-trade or other forms of free-market environmentalism"--Provided by publisher.
"Solving the Climate Crisis through Social Change - Public Investment in Social Prosperity to Cool a Fevered Planet"--Provided by publisher.
Includes bibliographical references (p. [251]-282) and index.
Keywords: Public investments; Income distribution -- Government policy; Social change; Climatic changes